The Effect of Brand Love and Gamification on Repurchase Intention through Customer Engagement as an Intervening Variable in E-Commerce Companies in Indonesia - Lestari, Nining Wahyu; Fitri, Raisa; Prabowo, Suryo Hadi Wira (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
The growth of e-commerce has caused e-commerce-based companies to emerge, and business competition in the e-commerce industry is getting stronger. This makes companies compete to increase repurchase intention with positive brand love and the implementation of gamification in companies to encourage engagement. Thus, this study aims to test the effect of brand love and gamification on repurchase intention through customer engagement as an intervening variable on Shopee application users. The data collection technique used a questionnaire that had previously been tested for validity and reliability. This study involved 236 respondents, who were then analyzed using descriptive statistical analysis and PLS-SEM. The research findings show that brand love and gamification have a direct, positive, and significant effect on customer engagement and repurchase intention. In addition, brand love and gamification have an indirect effect on repurchase intention through customer engagement. This article also provides suggestions to the Shopee company based on the research findings.